Home Lessons, Foreign Tests: The Background and First Missionary Term of Florence Murray, Maritime Doctor in Korea - Brouwer, Ruth (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1995)
AbstractFlorence Murray (1894-1975) had a long and successful career as a medical missionary in Korea. Yet her first term in the Japanese colony (1921-1927) was a troubled one. Her difficulties arose in large part from her strong commitment to new western standards of medical professionalism in a setting where evangelization and, in the case of women doctors, a separate spheres approach, had previously been given priority in missionary medicine. This commitment is best understood as an outcome of the fusing of values derived from her stereotypically “Presbyterian” upbringing and her professional training rather than as a straightforward instance of secularization. It also provides the most useful context for understanding her changing orientalist discourse.